Peace and Security Issues in Southeast Asia - Magno, Alexander R. (Kasarinlan: Philippine Journal of Third World Studies, 2007)
Covering many various topics, this paper is intended as a backgrounder on peace and security issues in Southeast Asia. There is a focus on the five original countries composing the ASEAN: Indonesia, Malaysia, Singapore, Thailand, and in particular, the Philippines. The article goes through the unique characters of each country and intertwines their similarities and differences to explain the complicated histories of the region. Certain particular concerns such as US occupation, political polarization within the region, and the anxiety of a Muslim or Leftist revolt in western-minded countries are highlighted. These issues and the characteristics of Southeast Asia are assessed in regards to the affects on peace and security for the people as well as international politics.
Keywords: peace; security; southeast asia; peace issues; security issues; ASEAN; Southeast Asia; Leftist movements; US military bases